EVALUASI IMPLEMENTASI STANDAR PELAYANAN MINIMAL PADA PELAYANAN KESEHATAN DI INSTALASI RAWAT JALAN RUMAH SAKIT UMUM DAERAH KABUPATEN KLUNGKUNG TAHUN 2014 - I Nyoman Mudia (Jurnal Manajemen dan Bisnis, 2014)
Implementation of Minimum Service Standards (MSS) on health care in the hospitalis one of the efforts to improve public services in the field of health. SPM implementation aimsto improve the quality of health care services to the user community hospital. This study aimsto gain an overview of: 1) Implementation of SPM on health care in the Hospital OutpatientInstallation Klungkung, which include; types of doctors serving in the Polyclinic, the type ofservice in the installation jawlan Rawat, hours of service, long waiting time danpelayanantuberculosis services, 2) constraints or barriers to implementation of SPM in the hospital and3) Position the Klungkung regency government in the application of SPM in KlungkungHospitalThis study used qualitative methods, data collection techniques such as observation,interview and documentation. The data analysis technique used is descriptive analysis, whilechecking the validity of the data was done by using triangulation. Determination of informantsdone by the key person.The results showed that: 1) Implementation of MSS services in the Installationkesehaatn Hospital Outpatient Klungkung not optimal, 2) constraints or barriers encounteredin the application of SPM in Klungkung Hospital, among others, the lack of specialistpersonnel and facilities and equipment in the application of SPM still less, 3) The position ofthe Government in the application of SPM Kabuipaten Klungkung Klungkung DistrictHospital, as well as the owner and holder of the policy, as well as facilitators and evaluators.Suggestion to note are: 1) Increased commitment to pursue the application of SPMwith the addition of specialist doctors, 2) an increase in the application of SPM with regardstandards in service to the community.Keywords: Minimum Service Standards, Quality of public services & satisfaction indexcustomers.